PERTANGGUNGJAWABAN TINDAK PIDANA EKSPLOITASI SEKSUAL YANG DITUJUKAN TERHADAP KEINGINAN SEKSUAL DENGAN ORANG LAIN (Studi Putusan Nomor 332/Pid.Sus/2023/PN Tjk) - Debora Shintiya Br. Siagian; Aprinisa; Risti Dwi Ramasari (JOURNAL OF LAW AND NATION, 2026)
Sexual exploitation is one of the forms of sexual violence crimes that continues to develop alongside advances in information technology and changes in criminal patterns within society. This crime not only causes physical harm to victims but also results in prolonged psychological, social, and economic suffering. This study aims to analyze the criminal liability of perpetrators of sexual exploitation intended to satisfy another person's sexual desires and to examine the legal considerations employed by judges in Decision Number 332/Pid.Sus/2023/PN Tjk. The research addresses two main issues: the criminal liability of the offender and the judicial considerations underlying the imposition of criminal sanctions. This research employs both normative and empirical juridical approaches by utilizing primary data obtained through interviews and secondary data derived from statutory regulations, court decisions, legal literature, and scientific journals. The data were analyzed using a qualitative juridical method. The findings indicate that the defendant fulfilled all legal elements of the criminal offense of sexual exploitation as stipulated in Law Number 12 of 2022 concerning Crimes of Sexual Violence and therefore bears criminal responsibility. The court imposed a sentence of one year imprisonment and a fine of IDR 5,000,000 based on juridical, philosophical, and sociological considerations. The judgment was founded upon valid legal evidence, the objectives of criminal punishment, victim protection, and both aggravating and mitigating circumstances. This study is expected to contribute to the development of criminal law, particularly regarding the enforcement of laws against sexual exploitation offenses in Indonesia.